Development of Tourism Potential Management in Improving Community Understanding Through A Tourism Awareness Education Pocket Book in Siboruon Village, Toba District - Naibaho, Wanton (LPPM IAKN Tarutung, 2024)
Tourism potential management is understood as part of village tourism potential management. Siboruon Waterfall as the potential of Siboruon Village has not been organized and developed by the local community, this is due to the lack of understanding of the village community towards the management of village tourism potential. For this reason, researchers formulate the problem 'how to increase public understanding of tourism potential management through tourism awareness education pocketbooks'. The purpose of this research is to develop tourism potential management to increase public understanding through tourism awareness education pocketbooks. The research method in this study uses the research and development method (Research and Development) of Borg and Gall through a 4D development procedure with a qualitative approach. This method is used to produce, develop products or perfect products. Travel awareness education pocketbook through the stages of development procedures guided by Borg and Gall research and development methods with the following stages: (1) Pre-Research and Collection of Data and Information; (2) Planning; (3) Product Development; (4) small-scale trials; (5) Product Revisions; (6) Wider scale test; (7) Product Improvement; (8) Material and Design Validation Test; (9) Final Product. This book contains tourism material, tourism potential management and tourism village potential in Siboruon village, where this pocket book was tested on the Siboruon village community and the result was an increase in community understanding of tourism potential management, this is evidenced by the increase in pretest and posttest scores. The conclusion of the study is that the development of tourism potential management through tourism awareness education pocketbooks can increase community understanding in Siboruon village, Toba Regency. This pocketbook is a means of education for the community to increase public understanding of tourism potential management. Researchers hope that this pocketbook can be carried out further product development, to future researchers and continue this research on larger product implementation tests to obtain stronger empirical evidence on the effectiveness and influence of the developed product.